The Role of the Teacher in Documenting Summative Assessment in Primary Education - Shqipe Avdiu-Kryeziu; Mensur Neziri (Human Research in Rehabilitation)
The purpose of this research was to obtain teachers' attitudes about the role of teachers in documenting summative assessment in primary education, focusing on the use and design of assessment instruments, planning summative assessment and informing students. The research has a qualitative approach and was carried out through semi-structured interviews with 20 primary education teachers. The results from this research show that teachers play an important role in documenting summative assessment, using different assessment instruments and adapting them to curriculum requirements. Also, the research emphasizes the importance of informing students and parents about the summative assessment process to ensure transparency and support in student development. Knowing how important and necessary assessment is in the learning process, we carried out this research, which brings innovation with its findings and serves teachers, parents, researchers from the fields of education and all actors who participate in the student assessment process.